Study of Ki67 proliferation index association with clinico-pathological features of non-Hodgkin’s lymphoma at Tishreen University Hospital - ابراهيم عزه; فراس حسين; سامر عاقل (Latakia University Journal -Medical Sciences Series, 2022)
Purpose : we aim to study the Correlation between the Proliferative index Ki67 and clinical variables (staging ,B symptoms ), demographic variables (age , sex) , histologic variables (subtype of NHL , anatomic site , extra nodal involvement , bone marrow involvement ) in NHL patients . Method: the study sample consisted of 90 patients who were admitted and treated at the Cancer Treatment Center in Tishreen University Hospital between 2015 and 2020 , we did a retrospective study on the files of NHL lymphoma patients who achieved the inclusion criteria and studied the previous variables and Ki67 Results: the value of Ki67 was between 3% and 100% with a median value approximates 50,2%±26,2% . we divided patients into two groups depending on the value of Ki67 : ≥45% and <45% , the we compared the previous variables with this two groups . the difference of age and sex between the two Ki67 value groups were not statically (P-value :0,311/0,449 in respect ) or clinically significant , so as the staging according to the Ann Arbor staging system ( P-value:0,207) . we noticed that there was a significant association to the subtypes of NHL , the value of Ki67≥45% was associated with DLBCL ، Burkit ، High Grade B Cell . whereas the value of Ki67<45% were associated basically with FL ، SLL ، Small B Cell ، T Cell Rich B Cell with astatically importance ( p-value : 0,006) . lastly the value of Ki67≥45% was associated with high levels of extra nodal sites (P-value: 0,001) , B symptoms (P-value : 0,020 ) , bone marrow involvement (P-value: 0,001) and high levels of LDH (P-value:0,001) . Conclusion : our study showed that there was significant association between high values of Ki67 (≥45%) and the more aggressive subtypes of NHL and also with positive extra nodal sites ,B symptoms and bone marrow involvement .